Antecedents of Tourists’ Environmentally Responsible Behavior: The Perspective of Awe - Jiang, Juan; Gao, Bo Wendy; Su, Xinwei (Frontiers in Psychology, 2022)
The promotion of tourists’ environmentally responsible behavior (TERB) plays a central role in destination management for sustainability. Based on the stimulus–organism–response framework, this study proposes an integrated model for behavior management by examining the relationship between stimuli (natural environment and availability of infrastructure) and response factors (satisfaction and TERB) through the organism (the emotion of awe). Survey data from 458 tourists visiting Mount Heng in Hunan Province, Southern China, were used to empirically evaluate the proposed framework. The findings demonstrate that the perception of a destination’s natural environment positively impacts tourists’ sense of awe and satisfaction; the perception of availability of infrastructure positively and significantly influences awe, satisfaction, and TERB; and awe positively impacts satisfaction and TERB. Moreover, the emotion of awe plays a significant mediating role in this proposed model. The theoretical significance of this study and the implications for tourism destinations are discussed.